Anti-RO/SSA and anti-La/SSB antibodies: Association with mild lupus manifestations in 645 childhood-onset systemic lupus erythematosus - Novak, Glaucia V.; Marques, Mariana; Balbi, Verena; Gormezano, Natali W.S.; Kozu, Kátia; Sakamoto, Ana P.; Pereira, Rosa M.R.; Terreri, Maria T.; Magalhães, Claudia S. [UNESP]; Guariento, Andressa; Sallum, Adriana M.E.; Marini, Roberto; et al. (Elsevier, 2017)
Background To our knowledge there are no studies assessing anti-Ro/SSA and anti-La/SSB autoantibodies in a large population of childhood-systemic lupus erythematosus (cSLE) patients. Methods This was a retrospective multicenter cohort study performed in 10 Pediatric Rheumatology services, São Paulo state, Brazil. Anti-Ro/SSA and anti-La/SSB antibodies were measured by enzyme linked immunosorbent assay (ELISA) in 645 cSLE patients. Results Anti-Ro/SSA and anti-La/SSB antibodies were evidenced in 209/645 (32%) and 102/645 (16%) of cSLE patients, respectively. Analysis of cSLE patients with and without anti-Ro/SSA antibodies revealed higher frequencies of malar rash (79% vs. 71%, p = 0.032), photosensitivity (73% vs. 65%, p = 0.035), cutaneous vasculitis (43% vs. 35%, p = 0.046) and musculoskeletal involvement (82% vs. 75%, p = 0.046) in spite of long and comparable disease duration in both groups (4.25 vs. 4.58 years, p = 0.973). Secondary Sjögren syndrome was observed in only five patients with this antibody (2.5% vs. 0%, p = 0.0035), two of them with concomitant anti-La/SSB. The presence of associated autoantibodies: anti-Sm (50% vs. 30%, p < 0.0001), anti-RNP (39% vs. 21%, p < 0.0001) and anti-ribossomal P protein (46% vs. 21%, p = 0.002) was also significantly higher in patients with anti-Ro/SAA antibodies. Further evaluation of cSLE patients with the presence of anti-La/SSB antibodies compared to those without these autoantibodies showed that the frequency of alopecia (70% vs. 51%, p = 0.0005), anti-Sm (59% vs. 31%, p < 0.0001) and anti-RNP (42% vs. 23%, p < 0.0001) were significantly higher in the former group. Conclusions Our large multicenter cohort study provided novel evidence in cSLE that anti-Ro/SSA and/or anti-La/SSB antibodies were associated with mild manifestations, particularly cutaneous and musculoskeletal. Secondary Sjögren syndrome was rarely observed in these patients, in spite of comparable frequencies of anti-Ro/SSA and/or anti-La/SSB reported for adult SLE.
Keywords: Anti-La/SSB autoantibodies; Anti-Ro/SSA autoantibodies; Multicenter cohort; Sjögren syndrome and childhood-systemic lupus erythematosus